PELUANG DAN TANTANGAN KOMPETENSI PERADILAN AGAMA PASCA AMANDEMEN UNDANG-UNDANG NOMOR 7 TAHUN 1989 TENTANG PERADILAN AGAMA - Abu Tolhah (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2016)
The development of religious court in Indonesia is existing while the establishment of Islamic law as part of national law system. It is influenced by the improvement of legal thought which is the background of Islamic law legislation. In independence period, exactli on 1970, the government emphasizes the existence of religious court through the law of court institution number 14 of 1970. On 1977, Indonesian Supreme Court pusblished the rule of Islamic court through the law number 7 of 1989 in which give the religious court for casation to supreme court.